Sound choices for development: the impact of public investments in rural India and China - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
Rural poverty in India and China has declined substantially in recent decades. This welcome development has come about largely because governments in both countries have invested in agricultural research, education, infrastructure, and other areas important to the rural poor. But what kinds of investments have reduced poverty the most? A clear answer to this question can help policymakers invest limited resources in ways that most benefit the poor. Recent studies by IFPRI and collaborators in India and China show that different kinds of rural public investment pay a range of dividends. Developing countries can significantly reduce rural poverty, stimulate agricultural growth, and move toward food security if they recognize that public investments are indispensable tools for achieving these ends and if they make the right investments.The research also reveals, in stark contrast to conventional thinking, that investments in low-potential lands can bring equal, if not greater, returns to investments in high-potential lands.